Method for testing heat-conducting property of graphene oxide composite well cementing material
By setting different graphene oxide ratios and molding and curing conditions, a non-steady state heat transfer model of thermal flow-solid coupling in geothermal wells is constructed, and the thermal conductivity of graphene oxide composite cementing materials is quantitatively analyzed, which solves the problem of difficulty in comprehensively and systematically analyzing the thermal conductivity of materials in the existing technology, and achieves more accurate heat transfer behavior simulation and optimized design.
Patent Information
- Application Number
- CN202510303969.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing thermal conductivity testing methods of graphene oxide composite cementing materials are difficult to comprehensively and systematically analyze the thermal conductivity of materials under various actual conditions, and the thermal conductivity behavior of simulating the heat transfer behavior in complex environments is not accurate enough.
By setting different graphene oxide ratios and molding and curing conditions, samples of multiple composite cementing materials are obtained, and non-steady-state heat transfer model of geothermal well thermal flow-solid coupling are constructed, the thermal resistance effect of the material is quantitatively analyzed, and the thermal conductivity performance model is established, and the thermal conductivity performance of the material is analyzed under different conditions by combining experiments and models.
A comprehensive and systematic analysis of the thermal conductivity of graphene oxide composite cementing materials under various actual conditions is achieved, the heat transfer behavior in complex environments is simulated, more accurate analysis results and optimization solutions are provided, and the scientificity and accuracy of material design is improved.
Smart Images

Figure CN119959295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a thermal conductivity technology of a composite cementing material, and in particular to a method for testing the thermal conductivity of a graphene oxide composite cementing material. Background Art
[0002] A method for testing the thermal conductivity of graphene oxide composite cementing materials is to prepare a series of composite cementing material samples by setting different graphene oxide ratios and molding and curing conditions; based on the thermal-fluid-solid coupling relationship of geothermal wells, a non-steady-state heat transfer model is constructed to simulate the heat transfer process of materials under medium-deep geothermal well conditions; at the same time, under variable temperature and pressure curing conditions, the influence of the external addition amount, orientation distribution and water-solid ratio of graphene oxide on the thermal conductivity of the material is analyzed, and a corresponding thermal conductivity model is established. Finally, the sample data is substituted into the model to quantitatively analyze the thermal resistance effect of the material under different conditions to optimize the thermal conductivity of the material.
[0003] The thermal conductivity testing methods of graphene oxide composite cementing materials on the market usually include two means: experimental testing and numerical simulation. In terms of experimental testing, common methods include thermal conductivity testers, which evaluate the thermal conductivity of materials by measuring the thermal conductivity coefficient of materials under different temperature and pressure conditions. At the same time, the thermal response of the samples in a simulated cementing environment will also be measured to further verify the heat transfer characteristics of the materials in practical applications. In terms of numerical simulation, researchers often construct multi-field coupled heat transfer models and combine the physical properties of the materials to predict and optimize the thermal conductivity of the materials. These test methods can provide the thermal conductivity characteristics of graphene oxide composite cementing materials under different working conditions, providing a scientific basis for the optimal design and engineering application of the materials. Summary of the invention
[0004] In order to improve the existing test methods for thermal conductivity of cementing materials, a test method for thermal conductivity of graphene oxide composite cementing materials is provided. Through different proportions and curing conditions, the thermal conductivity of the material is systematically analyzed to provide complete data support. The heat transfer behavior in complex environments is simulated by using the thermal-fluid-solid coupling model, which is closer to practical applications. The influence of various factors on thermal conductivity is quantified to help optimize the design. Combined with experiments and models, the thermal resistance effect is quantitatively analyzed to provide optimization solutions.
[0005] In order to achieve the above purpose, the technical solution adopted by the present invention is:
[0006] A method for testing thermal conductivity of graphene oxide composite cementing materials, characterized by comprising:
[0007] Based on different ratio settings and molding and curing conditions, different types of graphene oxide composite cementing material samples are obtained;
[0008] Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, an unsteady-state heat transfer model of geothermal wells with thermal fluid-solid coupling was constructed, and the thermal resistance effect of graphene oxide composite cementing materials was quantitatively analyzed.
[0009] A thermal conductivity model was established based on the effects of graphene oxide dosage, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions.
[0010] The parameter data of different types of samples were substituted into the thermal conductivity model to analyze the thermal conductivity of graphene oxide composite cementing materials under different conditions.
[0011] Preferably, obtaining different types of graphene oxide composite cementing material samples based on different ratio settings and molding and curing conditions specifically includes:
[0012] Select different raw materials based on the number of graphene oxide layers, the content of graphene oxide, the type of cement, and the type of dispersant;
[0013] Samples of graphene oxide composite cementing materials were classified based on mold shape, molding process, and curing temperature.
[0014] Preferably, the construction of a non-steady-state heat transfer model of geothermal well thermal fluid-solid coupling based on the heat transfer process of mid-deep geothermal wells and their multi-field coupling relationship, and the quantitative analysis of the thermal resistance effect of graphene oxide composite cementing materials specifically include:
[0015] The heat transfer process of the mid-deep geothermal well and its multi-field coupling relationship specifically include:
[0016] The heat conduction of the stratum affects the distribution of the temperature field;
[0017] The thermal conductivity of cementing materials and their thermal resistance effect affect the conduction of heat through the wellbore wall;
[0018] The heat convection and conduction of the fluid in the wellbore determine the heat extraction capacity;
[0019] Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, the control equations, boundary conditions and initial conditions are derived, and an unsteady-state heat transfer model of geothermal wells with thermal fluid-solid coupling is constructed.
[0020] By introducing the thermal resistance R c , quantitatively analyze the thermal resistance effect of graphene oxide composite cementing materials, the thermal resistance formula is Where L c is the cementing material thickness, k c is the thermal conductivity of cementing material, A c is the cross-sectional area of the cementing material, and ΔT is the changing temperature.
[0021] Preferably, the heat transfer process of mid-deep geothermal wells and their multi-field coupling relationship are used to derive the control equations, boundary conditions and initial conditions, and to construct a non-steady-state heat transfer model of geothermal well thermal fluid-solid coupling, which specifically includes:
[0022] The temperature distribution in the formation is dominated by heat conduction, and its governing equation is:
[0023]
[0024] Among them, ρ s is the formation density, C s is the formation specific heat capacity, k s is the formation thermal conductivity, T s is the formation temperature, t is the time;
[0025] The heat conduction process of graphene oxide composite cementing materials needs to consider its thermal conductivity. The heat conduction equation is:
[0026]
[0027] Among them, ρ c is the density of cementing material, C c is the specific heat capacity of cementing material, k c is the thermal conductivity of cementing material, T c is the cementing material temperature, t is the time;
[0028] The temperature change of the wellbore fluid is related to both the thermal convection and thermal conductivity of the fluid. The heat transfer equation of the fluid is:
[0029]
[0030] Among them, ρ f is the fluid density, C f is the specific heat capacity of the fluid, V is the fluid velocity, k f is the thermal conductivity of the fluid, T f is the fluid temperature;
[0031] The boundary conditions and initial conditions are specifically:
[0032] Outer boundary of the stratum: surface temperature T ∞ is a known constant;
[0033] When the outer surface of the cementing material contacts the formation, the continuity of heat flow is met:
[0034] Wellbore fluid inlet temperature T in As a known condition, the outlet temperature T out It can be inferred by temperature gradient;
[0035] At time t=0, the temperature distribution of the formation, cementing material, and wellbore fluid is known.
[0036] Preferably, the thermal conductivity model established based on the influence of the amount of graphene oxide added, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions specifically includes:
[0037] Based on the effective medium theory of the classical mixture model, the influence of the amount of graphene oxide on the thermal conductivity of the composite cementing material is obtained. The effective medium theory formula is:
[0038]
[0039] Among them, k com is the thermal conductivity of the composite cementing material, k base is the thermal conductivity of the matrix material (cement), k GO is the thermal conductivity of graphene oxide, is the volume fraction of graphene oxide, calculated as:
[0040]
[0041] This formula assumes that graphene oxide is uniformly mixed with the matrix material and there is no obvious interface effect between the two;
[0042] Based on the known orientation distribution of graphene oxide, the influence of orientation distribution on the thermal conductivity of composite cementing materials is obtained through a modified model. The modified model is:
[0043]
[0044] Among them, α is the correlation coefficient with the degree of alignment of graphene oxide, θ is the orientation angle of the curing graphene, is the volume fraction of graphene oxide;
[0045] Based on the correction formula, the influence of water-solid ratio on the thermal conductivity of composite cementing materials is obtained. The correction formula is:
[0046]
[0047] Where k0 is the basic thermal conductivity, α is the empirical constant between water-to-solid ratio and thermal conductivity, and W / S is the water-to-solid ratio;
[0048] Based on the Arrhenius model, the influence of temperature on the thermal conductivity of composite cementing materials is obtained. The Arrhenius model formula is:
[0049]
[0050] Among them, E αis the activation energy, which indicates the sensitivity of temperature to thermal conductivity, R is the gas constant, and T is the absolute temperature;
[0051] The effect of pressure can be expressed by introducing a correction factor for the material's density:
[0052] k com (P) = k base (1+βP)
[0053] Where β is a constant related to the compression of the material and P is the applied pressure;
[0054] Based on all influencing factors, a complete thermal conductivity model is obtained:
[0055]
[0056] Preferably, substituting parameter data of different types of samples into the thermal conductivity model to analyze the thermal conductivity of the graphene oxide composite cementing material under different conditions specifically includes:
[0057] Substituting each sample into the thermal conductivity model to calculate the thermal conductivity, the thermal conductivity of each sample at different temperatures, pressures and graphene oxide contents was obtained;
[0058] Based on the thermal conductivity of each sample under various conditions, the thermal conductivity model is optimized by appropriately adjusting the addition amount, orientation distribution, and water-solid ratio of graphene oxide.
[0059] Compared with the prior art, the advantages of the present invention are:
[0060] The present invention proposes a method for testing the thermal conductivity of graphene oxide composite cementing materials. By combining different ratio settings and molding and curing conditions, the thermal conductivity of graphene oxide composite cementing materials under various actual conditions can be systematically analyzed, providing comprehensive experimental data support for material design. Based on the thermal-fluid-solid coupled non-steady-state heat transfer model of geothermal wells, the heat transfer behavior of materials in complex environments can be more accurately simulated and predicted, providing analysis results that are closer to practical applications. By quantifying the effects of graphene oxide addition, orientation distribution and water-solid ratio on thermal conductivity, an accurate thermal conductivity model is established, which can deeply understand the effects of various factors on the thermal conductivity of materials and provide a theoretical basis for optimal design. By combining model calculations with experimental data, the thermal resistance effect of materials can be quantitatively evaluated, providing a specific optimization solution for designing composite cementing materials with excellent thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is a schematic flow chart of the thermal conductivity testing steps of the method proposed in the present invention;
[0062] Figure 2A schematic diagram of the test sample acquisition process of the method proposed in the present invention;
[0063] Figure 3 A schematic diagram of thermal resistance effect analysis of the method proposed in the present invention;
[0064] Figure 4 A schematic diagram of constructing a non-steady-state heat transfer model for the method proposed in the present invention;
[0065] Figure 5 A schematic diagram of building a thermal conductivity performance model of the method proposed in the present invention;
[0066] Figure 6 Schematic diagram of performance acquisition and optimization of the method proposed in the present invention. DETAILED DESCRIPTION
[0067] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0068] A method for testing thermal conductivity of graphene oxide composite cementing materials, comprising:
[0069] Step 1: Obtain different types of graphene oxide composite cementing material samples based on different ratio settings and molding and curing conditions;
[0070] Step 2: Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, an unsteady-state heat transfer model of geothermal well thermal fluid-solid coupling is constructed, and the thermal resistance effect of graphene oxide composite cementing materials is quantitatively analyzed;
[0071] Step 3: Establish a thermal conductivity model based on the effects of graphene oxide dosage, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions;
[0072] Step 4: Substitute the parameter data of different types of samples into the thermal conductivity model to analyze the thermal conductivity of graphene oxide composite cementing materials under different conditions.
[0073] See also Figure 2 As shown in the figure, based on different ratio settings and molding and curing conditions, different types of graphene oxide composite cementing material samples are obtained, including:
[0074] Select different raw materials based on the number of graphene oxide layers, the content of graphene oxide, the type of cement, and the type of dispersant;
[0075] Samples of graphene oxide composite cementing materials were classified based on mold shape, molding process, and curing temperature.
[0076] Specifically, when setting the proportion, determine the amount of graphene oxide (such as 0%, 0.05%, 0.1%, 0.2%, 0.5%), and set the water-solid ratio gradient (such as 0.4, 0.45, 0.5), while keeping the dosage of other admixtures consistent to reduce the interference of experimental variables. When mixing cement, mix water, graphene oxide dispersion and cement according to the designed proportion and stir until uniform (stir at low speed for 2 minutes and stir at high speed for 2 minutes). During molding and curing, inject the mixed slurry into the mold, shake it to remove bubbles, and initially cure it under standard conditions for 24 hours (temperature 25°C, humidity 95%). Then transfer it to a variable temperature and pressure curing device for curing under different temperature and pressure conditions (such as temperature 40°C, 80°C, 120°C, pressure 10MPa, 20MPa).
[0077] See also Figure 3 As shown in the figure, based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, a non-steady-state heat transfer model of geothermal well thermal fluid-solid coupling is constructed, and the thermal resistance effect of graphene oxide composite cementing materials is quantitatively analyzed. Specifically, it includes:
[0078] The heat transfer process of the mid-deep geothermal well and its multi-field coupling relationship specifically include:
[0079] The heat conduction of the stratum affects the distribution of the temperature field;
[0080] The thermal conductivity of cementing materials and their thermal resistance effect affect the conduction of heat through the wellbore wall;
[0081] The heat convection and conduction of the fluid in the wellbore determine the heat extraction capacity;
[0082] Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, the control equations, boundary conditions and initial conditions are derived, and an unsteady-state heat transfer model of geothermal wells with thermal fluid-solid coupling is constructed.
[0083] By introducing the thermal resistance R c , quantitatively analyze the thermal resistance effect of graphene oxide composite cementing materials, the thermal resistance formula is Where L c is the cementing material thickness, k c is the thermal conductivity of cementing material, A c is the cross-sectional area of the cementing material, and ΔT is the changing temperature.
[0084] It is understandable that the non-steady-state model of thermal-fluid-solid coupling has a large amount of computation and involves the coupling of multiple physical fields, which may lead to computational difficulties. Therefore, the coupling equations can be simplified by ignoring some extremely small influencing factors (such as extremely small temperature gradients or pressure changes) to improve computational efficiency.
[0085] See also Figure 4As shown in the figure, based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, the control equations, boundary conditions and initial conditions are derived to construct an unsteady-state heat transfer model of geothermal well thermal fluid-solid coupling, which specifically includes:
[0086] The temperature distribution in the formation is dominated by heat conduction, and its governing equation is:
[0087]
[0088] Among them, ρ s is the formation density, C s is the formation specific heat capacity, k s is the formation thermal conductivity, T s is the formation temperature, t is the time;
[0089] The heat conduction process of graphene oxide composite cementing materials needs to consider its thermal conductivity. The heat conduction equation is:
[0090]
[0091] Among them, ρ c is the density of cementing material, C c is the specific heat capacity of cementing material, k c is the thermal conductivity of cementing material, T c is the cementing material temperature, t is the time;
[0092] The temperature change of the wellbore fluid is related to both the thermal convection and thermal conductivity of the fluid. The heat transfer equation of the fluid is:
[0093]
[0094] Among them, ρ f is the fluid density, C f is the specific heat capacity of the fluid, V is the fluid velocity, k f is the thermal conductivity of the fluid, T f is the fluid temperature;
[0095] The boundary conditions and initial conditions are specifically:
[0096] Outer boundary of the stratum: surface temperature T ∞ is a known constant;
[0097] When the outer surface of the cementing material contacts the formation, the continuity of heat flow is met:
[0098] Wellbore fluid inlet temperature T in As a known condition, the outlet temperature T out It can be inferred by temperature gradient;
[0099] At time t=0, the temperature distribution of the formation, cementing material, and wellbore fluid is known.
[0100] See also Figure 5 As shown in the figure, based on the influence of the amount of graphene oxide added, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions, the thermal conductivity model is established, which specifically includes:
[0101] Based on the effective medium theory of the classical mixture model, the influence of the amount of graphene oxide on the thermal conductivity of the composite cementing material is obtained. The effective medium theory formula is:
[0102]
[0103] Among them, k com is the thermal conductivity of the composite cementing material, k base is the thermal conductivity of the matrix material (cement), k GO is the thermal conductivity of graphene oxide, is the volume fraction of graphene oxide, calculated as:
[0104]
[0105] This formula assumes that graphene oxide is uniformly mixed with the matrix material and there is no obvious interface effect between the two;
[0106] Based on the known orientation distribution of graphene oxide, the influence of orientation distribution on the thermal conductivity of composite cementing materials is obtained through a modified model. The modified model is:
[0107]
[0108] Among them, α is the correlation coefficient with the degree of alignment of graphene oxide, θ is the orientation angle of the curing graphene, is the volume fraction of graphene oxide;
[0109] Based on the correction formula, the influence of water-solid ratio on the thermal conductivity of composite cementing materials is obtained. The correction formula is:
[0110]
[0111] Where k0 is the basic thermal conductivity, α is the empirical constant between water-to-solid ratio and thermal conductivity, and W / S is the water-to-solid ratio;
[0112] Based on the Arrhenius model, the influence of temperature on the thermal conductivity of composite cementing materials is obtained. The Arrhenius model formula is:
[0113]
[0114] Among them, E αis the activation energy, which indicates the sensitivity of temperature to thermal conductivity, R is the gas constant, and T is the absolute temperature;
[0115] The effect of pressure can be expressed by introducing a correction factor for the material's density:
[0116] k com (P) = k base (1+βP)
[0117] Where β is a constant related to the compression of the material and P is the applied pressure;
[0118] Based on all influencing factors, a complete thermal conductivity model is obtained:
[0119]
[0120] See also Figure 6 As shown, the parameter data of different types of samples are substituted into the thermal conductivity model to analyze the thermal conductivity of graphene oxide composite cementing materials under different conditions, including:
[0121] Substituting each sample into the thermal conductivity model to calculate the thermal conductivity, the thermal conductivity of each sample at different temperatures, pressures and graphene oxide contents was obtained;
[0122] Based on the thermal conductivity of each sample under various conditions, the thermal conductivity model is optimized by appropriately adjusting the addition amount, orientation distribution, and water-solid ratio of graphene oxide.
[0123] In summary, the advantages of the present invention are: the advantages of this method are its comprehensiveness and systematicity, and it can comprehensively evaluate the thermal conductivity of graphene oxide composite cementing materials under different conditions. First, by setting different ratios and molding curing conditions, various types of graphene oxide composite samples are obtained, so that the research can cover a wider range of process parameters and ensure the diversity and representativeness of the results. Secondly, the method constructs a non-steady-state heat transfer model of geothermal well thermal fluid-solid coupling, combines the actual heat transfer process of deep geothermal wells, simulates a complex multi-field coupling environment, and quantitatively analyzes the thermal resistance effect of graphene oxide composite materials, which provides accurate theoretical support for the practical application of materials in geothermal wells. The study also considers the influence of factors such as graphene oxide addition amount, orientation distribution, and water-solid ratio on thermal conductivity, and establishes a thermal conductivity model. By substituting the test data of different material samples into the model, the specific effects and changing trends of these factors on thermal conductivity can be analyzed under different temperature and pressure curing conditions. This multi-dimensional analysis not only improves the accuracy of the model, but also provides practical guidance for optimizing material formulations and improving their thermal conductivity.
[0124] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for testing the thermal conductivity of graphene oxide composite cementing materials, characterized in that: include: Based on different ratio settings and molding and curing conditions, different types of graphene oxide composite cementing material samples are obtained; Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, an unsteady-state heat transfer model of geothermal wells with thermal fluid-solid coupling was constructed, and the thermal resistance effect of graphene oxide composite cementing materials was quantitatively analyzed. A thermal conductivity model was established based on the effects of graphene oxide dosage, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions. The parameter data of different types of samples were substituted into the thermal conductivity model to analyze the thermal conductivity of graphene oxide composite cementing materials under different conditions.
2. The method for testing thermal conductivity of graphene oxide composite cementing materials according to claim 1, characterized in that: The methods of obtaining different types of graphene oxide composite cementing material samples based on different ratio settings and molding and curing conditions specifically include: Select different raw materials based on the number of graphene oxide layers, the content of graphene oxide, the type of cement, and the type of dispersant; Samples of graphene oxide composite cementing materials were classified based on mold shape, molding process, and curing temperature.
3. The method for testing thermal conductivity of graphene oxide composite cementing materials according to claim 1, characterized in that: Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, an unsteady-state heat transfer model of geothermal well thermal fluid-solid coupling is constructed, and the thermal resistance effect of graphene oxide composite cementing materials is quantitatively analyzed, specifically including: The heat transfer process of the mid-deep geothermal well and its multi-field coupling relationship specifically include: The heat conduction of the stratum affects the distribution of the temperature field; The thermal conductivity of cementing materials and their thermal resistance effect affect the conduction of heat through the wellbore wall; The heat convection and conduction of the fluid in the wellbore determine the heat extraction capacity; Based on the heat transfer process of deep geothermal wells and their multi-field coupling relationship, the control equations, boundary conditions and initial conditions are derived, and an unsteady-state heat transfer model of geothermal wells with thermal fluid-solid coupling is constructed. By introducing the thermal resistance R c , quantitatively analyze the thermal resistance effect of graphene oxide composite cementing materials, the thermal resistance formula is Where L c is the cementing material thickness, k c is the thermal conductivity of cementing material, A c is the cross-sectional area of the cementing material, and ΔT is the changing temperature.
4. A method for testing thermal conductivity of graphene oxide composite cementing materials according to claim 3, characterized in that: The heat transfer process of mid-deep geothermal wells and their multi-field coupling relationship are used to derive the control equations, boundary conditions and initial conditions, and to construct a non-steady-state heat transfer model of geothermal well thermal fluid-solid coupling, which specifically includes: The temperature distribution in the formation is dominated by heat conduction, and its governing equation is: Among them, ρ s is the formation density, C s is the formation specific heat capacity, k s is the formation thermal conductivity, T s is the formation temperature, t is the time; The heat conduction process of graphene oxide composite cementing materials needs to consider its thermal conductivity. The heat conduction equation is: Among them, ρ c is the density of cementing material, C c is the specific heat capacity of cementing material, k c is the thermal conductivity of cementing material, T c is the cementing material temperature, t is the time; The temperature change of the wellbore fluid is related to both the thermal convection and thermal conductivity of the fluid. The heat transfer equation of the fluid is: Among them, ρ f is the fluid density, C f is the specific heat capacity of the fluid, V is the fluid velocity, k f is the thermal conductivity of the fluid, T f is the fluid temperature; The boundary conditions and initial conditions are specifically: Outer boundary of the stratum: surface temperature T ∞ is a known constant; When the outer surface of the cementing material contacts the formation, the continuity of heat flow is met: Wellbore fluid inlet temperature T in As a known condition, the outlet temperature T out It can be inferred by temperature gradient; At time t=0, the temperature distribution of the formation, cementing material, and wellbore fluid is known.
5. The method for testing thermal conductivity of graphene oxide composite cementing materials according to claim 1, characterized in that: The thermal conductivity model established based on the influence of the amount of graphene oxide added, orientation distribution, and water-solid ratio on thermal conductivity under variable temperature and pressure curing conditions specifically includes: Based on the effective medium theory of the classical mixture model, the influence of the amount of graphene oxide on the thermal conductivity of the composite cementing material is obtained. The effective medium theory formula is: Among them, k com is the thermal conductivity of the composite cementing material, k base is the thermal conductivity of the matrix material (cement), k GO is the thermal conductivity of graphene oxide, is the volume fraction of graphene oxide, calculated as: This formula assumes that graphene oxide is uniformly mixed with the matrix material and there is no obvious interface effect between the two; Based on the known orientation distribution of graphene oxide, the influence of orientation distribution on the thermal conductivity of composite cementing materials is obtained through a modified model. The modified model is: Among them, α is the correlation coefficient with the degree of alignment of graphene oxide, θ is the orientation angle of the curing graphene, is the volume fraction of graphene oxide; Based on the correction formula, the influence of water-solid ratio on the thermal conductivity of composite cementing materials is obtained. The correction formula is: Where k0 is the basic thermal conductivity, α is the empirical constant between water-to-solid ratio and thermal conductivity, and W / S is the water-to-solid ratio; Based on the Arrhenius model, the influence of temperature on the thermal conductivity of composite cementing materials is obtained. The Arrhenius model formula is: Among them, E α is the activation energy, which indicates the sensitivity of temperature to thermal conductivity, R is the gas constant, and T is the absolute temperature; The effect of pressure can be expressed by introducing a correction factor for the material's density: k com (P)=k base ·(1+βP) Where β is a constant related to the compression of the material and P is the applied pressure; Based on all influencing factors, a complete thermal conductivity model is obtained:
6. The method for testing thermal conductivity of graphene oxide composite cementing materials according to claim 1, characterized in that: Substituting the parameter data of different types of samples into the thermal conductivity model to analyze the thermal conductivity of the graphene oxide composite cementing material under different conditions specifically includes: Substituting each sample into the thermal conductivity model to calculate the thermal conductivity, the thermal conductivity of each sample at different temperatures, pressures and graphene oxide contents was obtained; Based on the thermal conductivity of each sample under various conditions, the thermal conductivity model is optimized by appropriately adjusting the addition amount, orientation distribution, and water-solid ratio of graphene oxide.
Citation Information
Cited By
Density analysis-based method for detecting heat-conducting property of polyurethane structural adhesive
CN120846908A